A pressure sensor made of laser-induced graphene@carbon ink in a waste sponge substrate using novel and simple fabricaing process for health monitoring - Aoxun Liang; Weijie Liu; Yuanrui Cui; Peihua Zhang; Xinkun Chen; Junlong Zhai; Wenhao Dong; Xueye Chen (Sensing and Bio-Sensing Research)
This paper presents a laser-induced graphene (LIG)@ carbon ink sponge (GCS) pressure sensor. This sensor has the advantage of low cost, significantly reducing the manufacturing cost by using simple materials (carbon ink and sponge) and processes. It has a high linearity with R2 = 0.996, a high sensitivity S = 3.68 kPa−1, a response time of 400 ms, and a recovery time of 300 ms. Meanwhile, to reduce the interference of sweat and water vapor in a high-humidity environment, the hydrophobic Ecoflex material is selected and improved by using SiO2 for packaging, enhancing the practicability of the sensor. The sensor is soft in texture and suitable for human health monitoring, and can be attached to different parts of the human body to monitor various physiological signals. By monitoring the click frequency of the mouse and keyboard, the bending of the arm, the cough at the neck (analyzing its frequency, intensity, and time pattern), the mechanical parameters when walking at the center of the sole, the physiological signal of clenching the fist, and the pressure change when holding a water cup at the center of the palm, it provides a assistance for related fields such as motor function assessment, diagnosis of respiratory system diseases, disease diagnosis and rehabilitation treatment.